Semiotic Analysis of KORPRI Batik Design “Bhumi, Nusa, Sagara” - Latif Ahmad Fauzan (Arkus, 2023)
As a cultural heritage, batik has become a symbol of Indonesia's wealth that is recognized internationally. Batik symbolizes local wisdom and contains many philosophical and social values in Indonesian culture. Batik has a long history and is often used for ceremonial and ritual purposes. However, along with its development, Batik is also used as the official uniform of organizations, including the Indonesian Civil Service Corps (KORPRI). The latest KORPRI batik design is called bhumi, nusa, sagara, with unique characteristics, such as colors and patterns inspired by national values. The symbols and meanings in batik designs are closely related to the study of Communication Studies, especially Semiotics which discusses signs and meanings in a message. This study aimed to describe the visual symbols and the meaning of the message in KORPRI batik bhumi, nusa, sagara. This research is qualitative research using semiotic analysis from Charles Sanders Pierce. The triangle semiotic model is used to analyze the visual elements in the KORPRI batik designs. The results of this study indicate that the KORPRI bhumi, nusa, and sagara Batik designs blend patterns from various regions in Indonesia, which have philosophical meanings from their respective cultures. In conclusion, the designs on KORPRI bhumi, nusa, sagara batik contain very strong local wisdom values and can become the identity of the Indonesian nation.